THE PREVALENCE AND ASSOCIATED FACTORS OF STAPHYLOCOCCUS AUREUS COLONIZATION IN THE ORAL CAVITY OF ADULTS - Ali Nagi, Ibraheem Abduh; Howilah, Ahmed Abdullah; Al-Sanabani, Nesreen Fadel; AL-Haddad, Khaled A; Al-Shamahy, Hassan Abdulwahab; Madar, Ebtihal Mohamed; Al-Ghaffari, Khaled Mohammed (Universal Journal of Pharmaceutical Research, 2024)
Background and aims: Long-term carriers of S. aureus are thought to make up between 21% and 30% of the human population. The bacteria are present in the mouth mucous membrane, the lower reproductive tract of females, the nose, and the typical skin microbiota. S. aureus can cause a wide range of ailments, from mild skin infections like cellulitis, boils, carbuncles, folliculitis, abscesses and scalded skin syndrome. Finding the prevalence of S. aureus in the oral cavities of adult dental patients as well as any possible contributing factors was the aim of this study. Methods: One hundred patients—fifty-nine with natural teeth and fifty with prosthetics—who attended dental clinics run by the Sana’a University Faculty of Dentistry participated in a cross-sectional study. The buccal mucous membranes of both groups were sampled, and the swabs were cultured on both selective medium (Mannitol salt agar) and medium supplemented with 5% blood. After that, all cultured plates were incubated at 37°C with oxygen for 48 hours, after which the bacterial growth was identified using conventional techniques. Results: Compared to female patients (41%), male patients had an oral colonization rate of S. aureus of 58.9%; for the younger age group (24–34 years), it was 70% with OR=3.7 (p=0.003). There was a significant link (odds ratio = 4.9) between detachable prostheses, prosthesis wearers with more than six years of experience (OR=17, p<0.001), and smokers who regularly lit up (OR=7.3, p= 0.03). Furthermore, a significant association was discovered between the practice of consistently ingesting large amounts of sugar (OR=5.7, p=0.01) and the growth of S. aureus in the oral cavity. Conclusion Healthy persons had a high frequency of Staphylococcus aureus in their oral cavities, and the infection was linked to certain behaviors such as smoking, chewing Qat, using prostheses, and patients who were younger in age. Also, the study emphasizes how crucial it is to practice proper oral hygiene because Staphylococcus aureus can primarily cause possible systemic infections through the mouth cavity. Peer Review History: Received 3 February 2024; Revised 10 March 2024; Accepted 23 April; Available online 15 May 2024 Academic Editor: Dr. Marwa A. A. Fayed , University of Sadat City, Egypt, maafayed@gmail.com Reviewers: Dr. George Zhu, Tehran University of Medical Sciences, Tehran, Iran, sansan4240732@163.com Dr. Mohsen Ali Al-Hamzi, Thamar University, Factuality of Dentistry, Yemen. mohsenalhamzi@gmail.com